French Centrism after the 2022 Elections: Strategy and Prospects - Dmitry V. Shmelev (Современная Европа)
The article examines the political strategy of the centrist Democratic Movement (MoDem) party and its leader François Bayrou during the presidential and parliamentary elections of 2022 and at the beginning of the second presidency of Emmanuel Macron. At this stage, the MoDem is an important element of the ruling majority, having a stable fraction in the National Assembly, which has consolidated its influence against the background of the growing socio-economic crisis in the country. MoDem remains a unitary political structure, focused on the figure of Bayrou and his circle of close associates. In political terms, the party positions itself as the center-left, which gives it the opportunity to prevent the government majority from shifting to the right, influence the appointment of some figures in the government and express its point of view on current policy. Bayrou still defends the transition to a proportional electoral system, criticises the implementation of pension reform, and supports the environmental initiatives of the government. The main guideline for the centrists was the idea of “agreement” in order to prevent the imbalance in institutions and the deepening of the crisis in the country. At the same time, they are committed to the traditional Christian-democratic culture, which was expressed towards the issue of including the right to abortion in the Constitution. The prospects of MoDem and Bayrou will be determined by the new electoral cycle (municipal and regional elections), the level of local voter support and the political configuration within the majority (for example, an alliance with Eduard Philippe) in the context of the presidential elections of 2027.